2012
DOI: 10.1177/0021886312469254
|View full text |Cite
|
Sign up to set email alerts
|

Making Change Happen

Abstract: The success of organizational change increasingly depends on employees taking personal responsibility for change through effective adaptation to changing conditions and proactive anticipation of new challenges. In this study, we examined how work context features influence the change-oriented behaviors of adaptivity and proactivity in the workplace. We proposed several direct and moderating effects of job context variables on adaptive and proactive behaviors. We used a multilevel design and a unique data set w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(50 citation statements)
references
References 130 publications
(264 reference statements)
1
43
0
6
Order By: Relevance
“…Although relevant studies are scarce, past research incorporating both adaptivity and proactivity has tended to emphasize the differences between these two types of behavior (Ghitulescu, 2013;Griffin et al, 2007Griffin et al, , 2010; MarquesBuilding and sustaining proactivity 15 Quinteiro & Curral, 2012). Our research suggests a more complementary role for each construct.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Although relevant studies are scarce, past research incorporating both adaptivity and proactivity has tended to emphasize the differences between these two types of behavior (Ghitulescu, 2013;Griffin et al, 2007Griffin et al, , 2010; MarquesBuilding and sustaining proactivity 15 Quinteiro & Curral, 2012). Our research suggests a more complementary role for each construct.…”
Section: Discussionmentioning
confidence: 67%
“…We suggested that successful organizational change requires the interplay of adaptive and proactive behavior (see also Ghitulescu, 2013). Our study has highlighted that adaptivity is related to future proactivity, but has not investigated the extent to which these two behaviors contribute to positive outcomes for the organization or the individual.…”
Section: Building and Sustaining Proactivity 18mentioning
confidence: 97%
See 3 more Smart Citations